Comparison of Emotional Dispositions Between Street Gang and Non-Gang Prisoners - Mallion, Jaimee S. (Journal of interpersonal violence, 2021)
Effectively recognizing, identifying, and utilizing emotional stimuli is essential for successful social interactions, with deficits in these robustly identified as risk factors for offending. Psychological understanding of street gang membership is limited, particularly surrounding emotional dispositions distinguishing street gang from non-gang offenders. This study examined how street gang members compare with non-gang offenders on trait emotional intelligence (TEI), antisocial personality disorder (ASPD), callous–unemotional traits, anger rumination, and aggression. Recruited through volunteer sampling, participants included 73 (44 street gang and 29 non-gang) male offenders incarcerated at a U.K. Category C prison. Participants completed seven questionnaires assessing emotional dispositions, social desirability, and, consistent with the Eurogang definition, street gang membership. To compare participants’ demographics and identify the predictors of street gang membership, chi-square and discriminant function analyses were conducted. With a significant discriminant function, Λ = .80, χ2(6) = 14.96, p = .021, high levels of ASPD, anger rumination, and aggression and low levels of TEI predict street gang membership. Compared with non-gang prisoners, street gang prisoners did not differ on callous–unemotional traits, age, or ethnicity. Results suggest that, compared with non-gang prisoners, street gang members were more likely to possess dysfunctional emotional dispositions. Findings from this research have important implications in terms of developing interventions for street gang membership. Specifically, this research supports the need for gang-specific early intervention and prevention programs, with emotion-focused components. Ideas for future research are discussed, including the identification of further sociocognitive, personality, and emotional traits distinguishing street gang from non-gang offenders.